2014
DOI: 10.1021/jp500678n
|View full text |Cite
|
Sign up to set email alerts
|

Alanate Anion, AlH4: Photoelectron Spectrum and Computations

Abstract: The alanate anion, AlH4(-), was generated in the gas phase using a pulsed arc cluster ionization source. Its photoelectron spectrum was then measured with 193 nm photons. The spectrum consists of a broad feature, spanning electron binding energies from 3.8 eV to over 5.3 eV. This band reflects the photodetachment transitions between the ground state of the AlH4(-) anion and the ground state of its thermodynamically unstable neutral counterpart, AlH4. The vertical detachment energy (VDE) of AlH4(-) was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…Aluminum hydride cluster anions, Al n H m − , were generated in a pulsed arc cluster ionization source (PACIS) which has been described in detail elsewhere. [29][30][31][32] This source has proven to be a powerful tool for generating metal hydrides and their anions. [30][31][32][33][34][35][36][37] Briefly, a ∼30 µs duration, 150 V electric pulse was applied across an anode and a sample cathode, vaporizing aluminum atoms and forming a plasma.…”
Section: Methodsmentioning
confidence: 99%
“…Aluminum hydride cluster anions, Al n H m − , were generated in a pulsed arc cluster ionization source (PACIS) which has been described in detail elsewhere. [29][30][31][32] This source has proven to be a powerful tool for generating metal hydrides and their anions. [30][31][32][33][34][35][36][37] Briefly, a ∼30 µs duration, 150 V electric pulse was applied across an anode and a sample cathode, vaporizing aluminum atoms and forming a plasma.…”
Section: Methodsmentioning
confidence: 99%
“…To experimentally investigate the existence of these exotic homocatenated aluminum hydrides in the gas phase, it is bettert os tudy them in the form of ions. For the Li n Al n H 2n + 2 molecules, one could study the Li nÀ1 Al n H 2n + 2 À anion by losing one Li + counter ion from Li n Al n H 2n + 2 .W hen n = 1, AlH 4 À ,t he simplest monosilane/methane analogue, was first examined by anion photoelectrons pectroscopy [43] in the gas phase. The vertical detachment energy (VDE) of AlH 4 À is as high as 4.4 eV,i ndicating that it is very stable.…”
Section: Et Of Aluminum Into Siliconmentioning
confidence: 99%
“…For the Li n Al n H 2 n +2 molecules, one could study the Li n −1 Al n H 2 n +2 − anion by losing one Li + counter ion from Li n Al n H 2 n +2 . When n =1, AlH 4 − , the simplest monosilane/methane analogue, was first examined by anion photoelectron spectroscopy in the gas phase. The vertical detachment energy (VDE) of AlH 4 − is as high as 4.4 eV, indicating that it is very stable.…”
Section: Electronic Transmutation Of Group 13 Elements Into Group 14 mentioning
confidence: 99%
“…[1][2][3][4] More complex aluminum hydrides, however, may offer better prospects. Gas phase studies discovered and characterized hundreds of previously unknown aluminum hydride cluster anions, Al y H z − , [5][6][7][8][9][10][11] and with them their corresponding neutral aluminum hydride cluster compositions. Recent studies of the reactions between these aluminum hydride cluster anions and oxygen found that their products were overwhelmingly aluminum oxides.…”
Section: Photoelectron Spectroscopic Study Of Carbon Aluminum Hydridementioning
confidence: 99%
“…Calculated electronic structure-related values for these cluster systems agree well with those obtained from our spectra. Like their cousins, i.e., aluminum hydride clusters [5][6][7][8][9][10][11] and boron-aluminum-hydride clusters, 22 these carbon aluminum hydride clusters may provide insight into new classes of energetic materials.…”
mentioning
confidence: 99%